2003
DOI: 10.1093/ps/82.3.436
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-amylase supplementation of broiler diets based on corn

Abstract: A 42-d trial was conducted to study the influence of exogenous alpha-amylase on digestive and performance traits in broilers fed a corn-soybean meal diet. There were two treatments (control and alpha-amylase supplemented diet) and six replicates (14 Cobb male chicks caged together) per treatment. At 7 d of age, alpha-amylase supplementation improved daily gain by 9.4% (P < or = 0.05) and feed conversion by 4.2% (P < or = 0.01). At the end of the trial, birds fed the alpha-amylase-supplemented diet ate more and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
103
2
27

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(143 citation statements)
references
References 37 publications
11
103
2
27
Order By: Relevance
“…In other studies, a slightly higher viscosity of jejunal digesta of 21-day-old broilers receiving a diet with about 60% maize grain was reported (Gonzàlez-Alvarado et al, 2007). A similar pH level to that in our study was determined in 22-day-old broiler chickens receiving a diet with about 50% maize grain by Gracia et al (2003), while almost twice lower values were obtained by Gonzàlez-Alvarado et al (2007). The results of our study showed that differences in the composition of maize cultivars had no influence on the development of the gastrointestinal tract.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In other studies, a slightly higher viscosity of jejunal digesta of 21-day-old broilers receiving a diet with about 60% maize grain was reported (Gonzàlez-Alvarado et al, 2007). A similar pH level to that in our study was determined in 22-day-old broiler chickens receiving a diet with about 50% maize grain by Gracia et al (2003), while almost twice lower values were obtained by Gonzàlez-Alvarado et al (2007). The results of our study showed that differences in the composition of maize cultivars had no influence on the development of the gastrointestinal tract.…”
Section: Resultssupporting
confidence: 90%
“…Nonetheless, the significant negative correlation between IDF, amino acid digestibility, and AME N values suggest the antinutritional potency of the maize IDF fraction, possibly by a cage effect. Due to supplementation of the maize-based diets with different enzymes (xylanase, α-galactosidase, β-mannanase, pectinase, α-amylase), an improvement of broiler performance was reported (Gracia et al 2003;Cowieson, 2005). It can be attributed to release of the cage effect as well as to increased degradation of the cell walls and greater utilization of hexoses and pentoses from the small intestine.…”
Section: Resultsmentioning
confidence: 99%
“…Entretanto, em outro estudo com frangos de corte sob suplementação com enzima amilase, foram observados maior ganho diário de peso (P<0,05) e melhor conversão alimentar (P<0,05) (Gracia et al, 2003).…”
Section: Resultsunclassified
“…Nevertheless, performance parameters were positively affected during the first 14 days of life as well as during the entire experiment. Some authors (Mahagna et al, 1995;Gracia et al, 2003;Cowieson et al, 2004) suggested that the use of exogenous enzymes could improve bird performance via limiting endogenous amino acid loss. Cowieson et al (2004) suggest that endogenous losses decrease by enzymatic degradation of antinutritional factors.…”
Section: Discussionmentioning
confidence: 99%
“…Cowieson et al (2004) suggest that endogenous losses decrease by enzymatic degradation of antinutritional factors. Mahagna et al (1995) and Gracia et al (2003) proposed that exogenous amylase and protease may supplement endogenous production of enzymes. The above hypotheses seem to be supported by the better nitrogen retention after enzyme supplementation on day 14, as recorded in the present experiment.…”
Section: Discussionmentioning
confidence: 99%